Menghadapi Disinformasi Konten Berita Digital di Era Post Truth - Amin Aminudin (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The post-truth era is an era where people are faced with indifference to the truth so that lies can camouflage with the truth. In disseminating the breadth of information in this digital era, people are faced with the emergence of information disruption in technology. This study aims to see a portrait of reality from the process of adapting conventional information to digital that avoids disinformation in the post-truth era. The method used in this study is descriptive qualitative with a literature study approach, the paradigm used in this study is the paradigm of constructivism. The results of this study show that the use of digital platforms is considered a form of change from economic to conventional to digital aspects. Along with the development of technology, it turns out that it is also accompanied by a new problem called disinformation. Disinformation can circulate when false information is knowingly shared by someone to cause harm to others. Instead of battling traditional media, digital media platforms have found new synergies. For example, with the presence of Google founded the Digital News Initiative, and Facebook by launching the Facebook Journalism Project. Both approaches are aimed at combating disinformation and can promote high-quality information services. The process is not indifferent, but if we understand from the side of the algorithm on the wrong data, we can understand it. So that the degree of trust can only come from what we understand. So we have to speak wisely then with the skills we need to be able to navigate the world of digital media in a better direction. The media ecosystem that needs to be understood in the post-truth era includes. First, the concept of mediation describes a process of social change that comes along with the growing importance of media to all stakeholders. Second, at a time of digital accessibility and social media, we face a diversity of content sources and modes of interaction.